Prospects of Topoisomerase Inhibitors as Promising Anti-Cancer Agents - Prasanna Anjaneyulu Yakkala; Naveen Reddy Penumallu; Syed Shafi; Ahmed Kamal (MDPI AG, 2023)
Topoisomerases are very important enzymes that regulate DNA topology and are vital for biological actions like DNA replication, transcription, and repair. The emergence and spread of cancer has been intimately associated with topoisomerase dysregulation. Topoisomerase inhibitors have consequently become potential anti-cancer medications because of their ability to obstruct the normal function of these enzymes, which leads to DNA damage and subsequently causes cell death. This review emphasizes the importance of topoisomerase inhibitors as marketed, clinical and preclinical anti-cancer medications. In the present review, various types of topoisomerase inhibitors and their mechanisms of action have been discussed. Topoisomerase I inhibitors, which include irinotecan and topotecan, are agents that interact with the DNA-topoisomerase I complex and avert resealing of the DNA. The accretion of DNA breaks leads to the inhibition of DNA replication and cell death. On the other hand, topoisomerase II inhibitors like etoposide and teniposide, function by cleaving the DNA-topoisomerase II complex thereby effectively impeding the release of double-strand DNA breaks. Moreover, the recent advances in exploring the therapeutic efficacy, toxicity, and MDR (multidrug resistance) issues of new topoisomerase inhibitors have been reviewed in the present review.